ANALISIS STRATEGI PEMASARAN PERBANKAN SYARIAH (KASUS DI KABUPATEN BANYUMAS) - Dwita Darmawati; Ekaningtyas Widiastuti (Universitas Ahmad Dahlan, 2012)
This study aims to analyze aspects of the service, whether in accordance with customer expectations Islamic banks, in Banyumas region and to formulate appropriate marketing strategies. The sample used in this study amounted to 33 respondents, an Islamic bank customers in Banyumas. To answer the problem used a quantitative approach to analyzing the five dimensions of quality of banking services, using analytical tools IPA (Importance Performance Analysis). The results showed that Islamic banks in Banyumas has a good performance on the dimensions of assurance, empathy, and tangible. Major constraints experienced by Islamic banks in Banyumas associated with dimensions of responsiveness, while the dimensions of reliability has been able to provide the same services to the average consumer's expectations. Some implications are given based on the results of the study.